The Reliability of the Abstract Aptitude Sub-Scale of the Developed and Validated Aptitude Test for UTME Selection - Eyetan Voke; P.A.U Ossai (Universitas Negeri Makassar, 2025)
The reliability of aptitude tests is critical for ensuring fair and valid selection of candidates for higher education. This study investigated the reliability of the Abstract Aptitude Sub-Scale of a developed and validated aptitude test for UTME selection in Nigeria. Specifically, the study examined both internal consistency and test–retest reliability of the sub-scale. The research adopted a descriptive survey design and involved a sample of 200 senior secondary school students drawn from public and private schools in Delta State using purposive sampling. Data were collected through the 25-item Abstract Aptitude Sub-Scale and analyzed using Kuder-Richardson Formula 20 (KR-20), Cronbach’s alpha, item-total correlations, and Pearson correlation coefficient for test–retest reliability. Findings revealed that the sub-scale demonstrated high internal consistency, with KR-20 = 0.87 and Cronbach’s alpha = 0.88. Item-total correlations ranged from 0.35 to 0.58, indicating that all items contributed positively to the measurement of abstract reasoning. Additionally, the test–retest reliability was found to be excellent, with Pearson’s r = 0.89 and a low standard error of measurement (SEM = 1.1), demonstrating temporal stability over a two-week interval. These results confirm that the Abstract Aptitude Sub-Scale is a psychometrically sound instrument, capable of consistently and accurately assessing abstract reasoning ability among UTME candidates. The study concludes that the sub-scale is suitable for high-stakes educational assessment and recommends its adoption for national selection purposes, with periodic review to maintain its reliability. Further research is suggested to examine the predictive validity of the sub-scale in relation to academic performance in tertiary institutions.